1994
DOI: 10.1038/npp.1994.15
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Neurotoxicity after (±)3,4-Methylenedioxymethamphetamine (MDMA; “Ecstasy”): A Controlled Study in Humans

Abstract: (±)3,4-Methylenedioxymethamphetamine (MDMA; "Ecstasy"), an increasingly popular recreational drug, is known to damage brain serotonin 5-hydroxytryptamine (5-HT) neurons in experimental animals. Whether MDMA is neurotoxic in humans has not been established. Thirty MDMA users and 28 controls were admitted to a controlled inpatient setting for measurement of biologic and behavioral indexes of central 5-HT function. Outcome measures obtained after at least 2 weeks of drug abstinence included concentrations of mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
174
7
11

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(206 citation statements)
references
References 27 publications
14
174
7
11
Order By: Relevance
“…Given the well-known role of DA in modulating activity, it is possible that the reduced ambulation and rearing observed in the MDMA-treated animals was due to abnormalities in the dopaminergic system. In addition to the previously mentioned ability of high MDMA doses to acutely release catecholamines, longer lasting alterations in catecholaminergic function have been reported not only in mice (which are known to exhibit dopamine neurotoxicity following MDMA), but also in rats, monkeys, and humans exposed to this compound (Commins et al, 1987;Gerra et al, 2002Gerra et al, , 2003Mayerhofer et al, 2001;McCann et al, 1994;Ricaurte et al, 1992). Moreover, we recently found that the same MDMA binge regimen used in the present study (ie with a 1-h interdose interval) significantly reduced DA transporter binding in the striatum .…”
Section: Discussionmentioning
confidence: 94%
“…Given the well-known role of DA in modulating activity, it is possible that the reduced ambulation and rearing observed in the MDMA-treated animals was due to abnormalities in the dopaminergic system. In addition to the previously mentioned ability of high MDMA doses to acutely release catecholamines, longer lasting alterations in catecholaminergic function have been reported not only in mice (which are known to exhibit dopamine neurotoxicity following MDMA), but also in rats, monkeys, and humans exposed to this compound (Commins et al, 1987;Gerra et al, 2002Gerra et al, , 2003Mayerhofer et al, 2001;McCann et al, 1994;Ricaurte et al, 1992). Moreover, we recently found that the same MDMA binge regimen used in the present study (ie with a 1-h interdose interval) significantly reduced DA transporter binding in the striatum .…”
Section: Discussionmentioning
confidence: 94%
“…It indicates that MDMA's effect on spatial memory is not due to its action within the dopaminergic system. Though MDMA exerts its effects in the brain through a multitude of transmitter systems, it is generally assumed that MDMA induced memory deficits that are related to changes in serotonergic function (Bolla et al 1998;McCann et al 1994;Reneman et al 2002;Verkes et al 2001). The present data seem to support this general notion.…”
Section: Discussionmentioning
confidence: 99%
“…Improved impulse control during serotonergic suppletion seems in line with reports on impaired impulse control in heavy users of MDMA during periods of abstinence. Studies on serotonergic function in recreational MDMA users have repeatedly shown low levels of 5HIAA in CSF (Bolla et al, 1998;McCann et al, 1994;Peroutka et al, 1987;Ricaurte et al, 1990), reduced density of 5-HT transporters (Reneman et al, 2002) and blunted neuro-endocrine responses in serotonergic challenge tests (Gerra et al, 1998;McCann et al, 1999;Verkes et al, 2001) when compared to nondrug using controls. In addition, serotonergic depletion has been linked to behaviors characterized by impaired impulse control (Linnoila et al, 1983(Linnoila et al, , 1993.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that have examined the effect of MDMA on impulsivity in abstinent MDMA users have provided conflicting results. McCann et al (1994) reported a decrement in impulsivity ratings of MDMA users as measured by the Multidimensional Personality Questionnaire, whereas others reported elevated scores of impulsivity in heavy MDMA users, using different subjective measures of impulsivity (Butler and Montgomery, 2004;Morgan, 1998Morgan, , 2000Parrott, 2000). Elevated levels of impulsiveness have been associated with lower levels of 5HT and CSF-5HIA (Linnoila et al, 1983(Linnoila et al, , 1993 and with dopaminergic activation in the prefrontal cortex leading to a reduction in 'inhibitory control' over behavioral functions (Jentsch and Taylor, 1999).…”
Section: Introductionmentioning
confidence: 99%